A Cross Layer Video Transmission Scheme Combining Geographic Routing and Short-Length Luby Transform Codes. (13th August 2015) - Duan, Pengrui; Liu, Liang; Zhang, Zhao
Video transmission is a real challenge for wireless multihop networks with high packet loss rate. This paper proposes a cross layer video transmission scheme which combines the geographic routing in network layer and the short-length Luby transform (LT) codes in transport layer. We first analyze the effect of bit error rate (BER) on the retransmission load and the effect of payload length and LT symbols size on network efficiency. Then, based on the product of the link quality and the distance from destination, we design a routing metric for geographic routing. We further propose a cross layer transmission scheme, which adaptively adjusts payload length to encapsulate short-length LT encoded symbols and selects routes based on the new routing metric. The simulation results show that our cross layer scheme can decrease the decoding overhead and the packet loss rate, while improving the video transmission quality and the network efficiency.